Drought, change and resilience in South Africa’s arid and semi-arid rangelands - Vetter, Susanne (South African Journal of Science, 2009)
Droughts can have serious ecological and economic consequences and will pose an increasing challenge to rangeland users as the global climate is changing. Finding ways to reduce ecological and economic impacts of drought should thus be a major research thrust. Resilience, defined as the amount of perturbation a social or ecological system can absorb without shifting to a qualitatively different state, has emerged as a prominent concept in ecosystem ecology and more recently as a conceptual framework for understanding and managing complex social-ecological systems. This paper discusses the application and relevance of resilience to understanding and managing ecosystem change, and enhancing the capacity of land users to adapt to droughts. Drought can trigger vegetation change and factors such as grazing management can influence the likelihood of such transitions. Drought can cause differential mortality of perennial plants and this could provide an opportunity for rangeland restoration by opening up establishment sites for desirable species. The capacity of land users to cope with drought is influenced by the resilience of their agro-ecosystems, the diversity of livelihood options, access to resources and institutional support. By these criteria, current agricultural development approaches in South Africa, particularly in communal rangelands and areas of land reform, are unlikely to enhance land users’ resilience to drought and other perturbations.